Pengaruh Digitalisasi, Literasi Keuangan, dan Inklusi Keuangan Terhadap Keberlanjutan Usaha Mikro Kecil dan Menengah - Ajeng Ayunda Destiari (Magister Ilmu Akuntansi Universitas Jambi, 2024)
This study aims to analyze the influence of digitalization, financial literacy, and financial inclusion on the sustainability of micro, small, and medium enterprises (MSMEs). In the context of the digital era, technology adoption and financial management capabilities are important factors in supporting the competitiveness and sustainability of MSMEs. This study uses a quantitative approach with a survey method, involving a number of MSME respondents in various business sectors. Data were collected through questionnaires and analyzed using multiple linear regression to test the relationship between variables. The results of the study show that digitalization has a positive and significant effect on the sustainability of MSMEs through increased operational efficiency and market access. Financial literacy also has a positive effect, where the ability of MSME actors to manage finances, understand risks, and plan investments is the key to long-term success. In addition, financial inclusion, which includes access to banking services and financial institutions, has been shown to strengthen the financial stability of MSMEs. Simultaneously, these three variables have a significant contribution to improving the sustainability of MSMEs. This study concludes that digitalization, financial literacy, and financial inclusion are crucial elements in encouraging the resilience and growth of MSMEs amidst the dynamics of the modern economy. The implication of this research is the need for synergy between the government, financial institutions, and business actors to encourage the development of an ecosystem that supports digital transformation and financial inclusion for MSMEs.